Language and Consumer Dishonesty: A Self-Diagnosticity Theory - Gai, Phyliss Jia; Puntoni, Stefano (Journal of Consumer Research, 2021)
AbstractHow does foreign language influence consumer dishonesty? We propose a self-diagnosticity theory arguing that compared to one’s native language, using a foreign language makes lying appear less self-diagnostic, thereby increasing or decreasing lying depending on which aspect of the self is salient. In situations where lying reflects an undesirable, dishonest self, using a foreign language increases lying. In contrast, in situations where lying primarily reflects a desirable (e.g., competent or compassionate) self, using a foreign language decreases lying. Ten studies, spanning various languages, consumer contexts, and experimental paradigms, support the theory. The studies establish that the effect of language on lying jointly depends on the self-diagnosticity of lying and on whether lying is diagnostic of a positive or a negative aspect of the self. The findings highlight self-diagnosticity as a valuable lens to understand the behavior of bilingual consumers and offer practical guidance for addressing dishonesty in the marketplace.